The Leadership of R&D teams: signifi cance, challenges, complexity and reflection on the existing models - Radek, Patrycja (Przywództwo w zespołach B+R: istota, wyzwania, złożoność, 2019)
The literature in the leadership field covers extensive research, studies and compendia. However, only a small part of them are focused on leadership in research and development (R&D) teams working on innovations. Those authors who address the subject highlight the specifics of the scientists’ and engineers’ leadership engaged in creative work on innovation. Even less research and papers are connected with academic scientific teams searching for technology-based innovations, while one can recognize a research gap in the area of leadership, in sophisticated technology-based project teams like interdisciplinary or transdisciplinary teams. In this article was present a review of literature on leadership of innovative R&D teams. The goal of the article is to present a review of the literature in the area of leadership in R&D teams, along with a critical analysis of selected leadership models as well as an indication of the research interest and trends in terms of the described issues
Management Sciences = Nauki o Zarządzaniu, 2019, vol. 24, no. 2, s. 9-17
Keywords: leadership of innvation; R&D team; R&D organization; innovation; leadership model; przywództwo innowacji; zespół badawczo-rozwojowy; organizacja badawczo-rozwojowa; innowacja; model przywództwa